LISTENING TO NON-VERBAL CUES IN COMMUNICATION (Modern education and development, 2024)
Non-verbal communication plays a crucial role in understanding and interpreting messages beyond the spoken word. While verbal communication relies on language and words, non-verbal cues—such as body language, facial expressions, gestures, posture, and tone of voice—often convey more than what is said. This article explores the significance of non-verbal cues in communication, their impact on how messages are received, and how individuals can enhance their listening skills by attending to these cues. The study of non-verbal communication enriches interpersonal interactions, fostering clearer understanding and reducing the risk of miscommunication.